2015
DOI: 10.1038/ncb3149
|View full text |Cite
|
Sign up to set email alerts
|

ERBB2 triggers mammalian heart regeneration by promoting cardiomyocyte dedifferentiation and proliferation

Abstract: The murine neonatal heart can regenerate after injury through cardiomyocyte (CM) proliferation, although this capacity markedly diminishes after the first week of life. Neuregulin-1 (NRG1) administration has been proposed as a strategy to promote cardiac regeneration. Here, using loss- and gain-of-function genetic tools, we explore the role of the NRG1 co-receptor ERBB2 in cardiac regeneration. NRG1-induced CM proliferation diminished one week after birth owing to a reduction in ERBB2 expression. CM-specific E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
539
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(574 citation statements)
references
References 70 publications
32
539
2
1
Order By: Relevance
“…This is further supported by another study where they showed that Nrg1 lost its ability to promote cardiomyocyte proliferation after P7, concomitant with the postnatal down-regulation of its receptor Erbb2 (D'Uva et al, 2015).…”
Section: Cell-free Therapysupporting
confidence: 63%
See 1 more Smart Citation
“…This is further supported by another study where they showed that Nrg1 lost its ability to promote cardiomyocyte proliferation after P7, concomitant with the postnatal down-regulation of its receptor Erbb2 (D'Uva et al, 2015).…”
Section: Cell-free Therapysupporting
confidence: 63%
“…Interestingly, overexpression of constitutively active Erbb2 promoted neonatal and adult cardiomyocyte proliferation as well as adult cardiac function following MI (D'Uva et al, 2015).…”
Section: Cell-free Therapymentioning
confidence: 99%
“…Fang et al (17) had confirmed that NRG-1 can protect myocardium from IRI through a PI3K/Akt pathway. D' Uva et al (29) showed that selectively activating ErbB2 receptors on the myocardium can induce cardiomyocyte proliferation and improve the recovery of cardiac function, with less infarct size, more vascularization and less scarring.…”
Section: Endothelial Derived Nrg-1 May Be Essential For Ipc-induced Cmentioning
confidence: 99%
“…[17] In animal models of regeneration, cardiomyocyte dedifferentiation (with sarcomere disassembly) occurs as the first stage of proliferation and is triggered by hypoxia. [18,19] In humans, proliferation may stall due to persistent hypoxia or limited energetic substrate. [20,21] Following revascularisation, cardiomyocyte re-differentiation and proliferation has been observed, which may underlie functional recovery [22].…”
Section: Pathophysiology Of Hibernating Myocardiummentioning
confidence: 99%